Mempertahankan Kepuasan Pelanggan dan Switching Barrier Terhadap Customer Retention Produk Hanasui di Beauty Shoppy Jombang - Nadia Roudhotul Hilliyah; Lilis Sugi Rahayu Ningsih; Winaika Irawati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
Abstract. In an effort to create customer retention, the company improves product quality, service and purchasing power suitability so that consumers can feel satisfaction in using the product and create barriers to switching to Hanasui products at Beauty Shoppy Jombang. The purpose of this study is to determine the influence in maintaining customer satisfaction and switching barriers to customer retention in customers of Hanasui brand products at Beauty Shoppy Jombang by using quantitative methods. The total population in this study is 150 customers. This study uses multiple linear regression analysis techniques and hypothesis testing. The results of this study indicate that customer satisfaction and switching barriers have a significant effect on customer retention of Hanasui products at Beauty Shoppy Jombang.